2021
DOI: 10.3390/molecules26092663
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone Inhibits Helicobacter pylori Urease Activity

Abstract: Helicobacter pylori (H. pylori) produces urease in order to improve its settlement and growth in the human gastric epithelium. Urease inhibitors likely represent potentially powerful therapeutics for treating H. pylori; however, their instability and toxicity have proven problematic in human clinical trials. In this study, we investigate the ability of a natural compound extracted from Zingiber zerumbet Smith, zerumbone, to inhibit the urease activity of H. pylori by formation of urease dimers, trimers, or tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…[33] Recent studies sustain that zerumbone from Zingiber zerumbet, inhibits the urease activity of H. pylori by formation of urease dimers, trimers, or tetramers. [34] This kind of interaction seems to be a new form to change protein function by natural products from plants.…”
Section: Inhibitory Properties Of Snaf and Delphinidin-3-(pcoumaroyl)...mentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Recent studies sustain that zerumbone from Zingiber zerumbet, inhibits the urease activity of H. pylori by formation of urease dimers, trimers, or tetramers. [34] This kind of interaction seems to be a new form to change protein function by natural products from plants.…”
Section: Inhibitory Properties Of Snaf and Delphinidin-3-(pcoumaroyl)...mentioning
confidence: 99%
“…The turbidimetric method of triolein hydrolysis was used to determine V max and K m of PL. [34] The enzyme was adjusted to a final concentration of 150 μg mL À 1 (1 units mL À 1 ) in 100 mM Tris buffer pH 9.0, containing triolein (0.3 mM) sodium deoxycholate (20 mM), colipase (3 mg L À 1 ) and calcium chloride (0.02 mM). Enzymatic reactions had a final volume of 0.3 mL and were initiated by its incubation at 37 °C for 30 min with two concentrations (100 and 150 μg mL À 1 ) of SNAF, pure cyanidin-3-O-rutinoside-5-glucoside and pure petunidin-3-(cis-p-coumaroyl)-rutinoside-5-glucoside and different substrate concentrations (0.2-2.2 mM).…”
Section: Kinetic Assays With Rpaf and Purified Anthocyanins On Pancre...mentioning
confidence: 99%
“…It has an anti-virulence effect by inhibiting the biofilm formation and hyphal growth of Candida albicans in a concentration-dependent manner. In addition, it exhibits significant cytotoxic activity against lung, colon, leukemia, ovarian, skin, liver and breast cancers, with selective cytotoxic activity on human tumor cell lines, not found with the structural analogue, α-humulene, that lacks the carbonyl group ( Figure 1 ) [ 4 , 5 , 6 , 13 , 14 ]. Several studies have reported the antitumor activity of zerumbone in vitro, as well as in vivo models such as breast, colorectal, cervical, lung, renal cell carcinoma and skin cancers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors allow H. pylori to move within the viscous gastric mucosa, facilitate its attachment to epithelial cells and counteract the acidic environment of the human stomach. Also, the production of carbon dioxide (CO 2 ) and ammonia (NH 3 ) by urea hydrolysis, provides a nitrogen source for the bacterium (Cheok et al, 2021 ; Woo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%